Effect of Spiritual Intelligence on Intentions of Hospital-Maker Benefactors - mohammad javad naeiji; Fatemeh Gholami (Tehran University of Medical Sciences, 2017)
Background: Although the role of Spirituality has been acknowledged in the social entrepreneurship literature, we know of no research that has empirically investigated relationships between spiritual intelligence and health and care benefactors. Thus, this paper aims to propose and empirically test a theoretical model positing relationships among spiritual intelligence and intentions of hospital-makers benefactors. Materials & Methods: This study is descriptive which is conducted with total number of 164 hospital-makers benefactors, and is tested by path analysis. For measuring spiritual intelligence, three questionnaires distributed between every subject and two of his/her acquaintances. Results: The results suggest that spiritual intelligence and other related variables explained 41 per cent of the variance in the rate of hospital-makers benefactors intentions (R2=0/41) that is a sizable amount in behavioral studies. Results provide strong support for the proposition that social mission and social responsibility fully mediate the positive effect of spiritual intelligence on intentions of hospital-makers benefactor. Conclusion: With existence of opportunities for merely finical investments, hospital-makers benefactors should have high levels of spiritual intelligence to gain motivation for social wealth creation. Policy-makers of health system, to increase charitable activities, should focus on heightening spiritual intelligence in health and care sector.